ANALISIS MOTIF PROYEK PEMBANGUNAN REL KERETA API KUNMING-SINGAPURA (2015-2017) - Andi Wirapratama (Indonesian Association for International Relations, 2021)
ABSTRACT China is popularizing the Belt Road Initiative or abbreviated as BRI, which is an ambitious development plan involving many regions throughout the world. One of BRI's projects is the construction of the Kunming-Singapore railroad track. BRI's motives are still confusing between the economy and geopolitics. Not to mention, there is a paradox in China's leadership statement regarding BRI as a political or economic foreign policy tool. As a result, the railroad project also has a mixed motive. This research attempts to uncover the motive of Kunming-Singapore Railroad construction project. This study tries to analyze this phenomenon with three concepts, offensive realism, commercial liberalism, and Giovanni Arrighi's capitalism mode. The results of this study show that the railroad project has economic and geopolitical factors behind it. Economic and geopolitical factors are both dominating and complementing China's decision to invest in this project due to changes in the structure of the domestic and international economy and to maximize wealth in order to become a Great Power. Keywords: ABSTRAK Tiongkok sedang mempopulerkan Belt Road Initiative atau disingkat BRI, yang merupakan sebuah rencana pembangunan ambisius yang melibatkan banyak kawasan di seluruh dunia. Salah satu proyek BRI adalah pembangunan jalur rel kereta api Kunming-Singapura. Motif BRI saat ini masih simpang siur, antara ekonomi dan geopolitik. Belum lagi, ada paradoks dalam pernyataan kepemimpinan Tiongkok terkait BRI sebagai alat politik atau ekonomi. Walhasil, proyek jalur rel kereta api ini juga memiliki motif yang simpang siur. Penelitian ini mencoba untuk mengungkap proyek pembangunan Jalur Rel Kereta Api Kunming-Singapura. Penelitian ini mencoba menganalisis fenomena ini dengan tiga konsep, offensive realism, commercial liberalism, dan mode kapitalisme Giovanni Arrighi, Hasil dari penelitian ini memperlihatkan bahwa proyek jalur kereta api ini memiliki faktor ekonomi dan geopolitik yang melatarbelakanginya. Faktor ekonomi maupun geopolitik sama-sama mendominasi dan saling melengkapi keputusan Tiongkok untuk berinvestasi dalam proyek ini disebabkan karena perubahan struktur ekonomi domestik dan internasional serta berupaya untuk memaksimalkan kekayaan agar dapat menjadi Great Power. Kata kunci: BRI; RRC; Kunming; Singapura; rel kereta api.